Genetically Encoded, Functional Single‐Strand RNA Origami: Anticoagulant. Issue 21 (10th April 2019) - Krissanaprasit, Abhichart; Key, Carson; Fergione, Michael; Froehlich, Kristen; Pontula, Sahil; Hart, Matthew; Carriel, Pedro; Kjems, Jørgen; Andersen, Ebbe Sloth; LaBean, Thomas H.
Abstract: Nucleic acid aptamers selected for thrombin binding have been previously shown to possess anticoagulant activity; however, problems with rapid renal clearance and short circulation half‐life have prevented translation to clinical usefulness. Here, a family of self‐folding, functional RNA origami molecules bearing multiple thrombin‐binding RNA aptamers and showing significantly improved anticoagulant activity is described. These constructs may overcome earlier problems preventing clinical use of nucleic acid anticoagulants. RNA origami structures are designed in silico and produced by in vitro transcription from DNA templates. Incorporation of 2'‐fluoro‐modified C‐ and U‐nucleotides is shown to increase nuclease resistance and stability during long‐term storage. Specific binding to human thrombin as well as high stability in the presence of RNase A and in human plasma, comparatively more stable than DNA is demonstrated. The RNA origami constructs show anticoagulant activity sevenfold greater than free aptamer and higher than previous DNA weave tiles decorated with DNA aptamers. Anticoagulation activity is maintained after at least 3 months of storage in buffer at 4 °C. Additionally, inhibition of thrombin is shown to be reversed by addition of single‐stranded DNA antidotes. This project paves the way for development of RNA origami for potential therapeutic applications especially as a safer surgical anticoagulant. Abstract : A single‐molecule RNA origami bearing dual thrombin RNA aptamers is demonstrated. The functional RNA origami specifically binds to thrombin and inhibits the coagulation cascade. Reactivation of thrombin is observed following addition of complementary nucleic acid antidotes.